Profile of the Pleximmune blood test for transplant rejection risk prediction. (2nd April 2016) - Sindhi, Rakesh; Ashokkumar, Chethan; Higgs, Brandon W; Levy, Samantha; Soltys, Kyle; Bond, Geoffrey; Mazariegos, George; Ranganathan, Sarangarajan; Zeevi, Adriana
SUMMARY: The Pleximmune TM test (Plexision Inc., Pittsburgh, PA, USA) is the first cell-based test approved by the US FDA, which predicts acute cellular rejection in children with liver- or intestine transplantation. The test addresses an unmet need to improve management of immunosuppression, which incurs greater risks of opportunistic infections and Epstein–Barr virus-induced malignancy during childhood. High-dose immunosuppression and recurrent rejection after intestine transplantation also result in a 5-year graft loss rate of up to 50%. Such outcomes seem increasingly unacceptable because children can experience rejection-free survival with reduced immunosuppression. Pleximmune test sensitivity and specificity for predicting acute cellular rejection is 84% and 80% respectively in training set–validation set testing of 214 children. Among existing gold standards, the biopsy detects but cannot predict rejection. Anti-donor antibodies, which presage antibody-mediated injury, reflect late-stage allosensitization as a downstream effect of engagement between recipient and donor cells. Therefore, durable graft and patient outcomes also require accurate management of cellular immune responses in clinical practice.